Population growth and the environment: Can we eat the cake and have it? - Shmuel Amir (Discrete Dynamics in Nature and Society)
Continuous population growth and the concomitant maintenance of a growth sustaining environment are not in conflict only if the rates of both economic and biological processes are slowed down steadily. For this to happen, individual and social impatience-lowering adaptations should be adopted, and the capital of the system, both economic and natural, has to be redistributed among the system interacting components to result in an ever more complex organizational web. In addition, these factors have to corroborate with a third element, the incorporation of an arsenal of varied technological innovations that improves the use of existing stocks.